Wireless multihop communication in sparse Vehicular Ad-Hoc Networks. (22nd July 2009) - Oka, Hiroaki; Higaki, Hiroaki
In Intelligent Transport System (ITS), multiple vehicular mobile nodes cooperate through a wireless communication network. Here, data messages are transmitted along a multihop route with help of intermediate nodes. In an area with sparsely distributed nodes, mobility of a node carrying data messages also helps to achieve higher transmission ratio. This paper proposes a method for message transmission along a sequence of street segments detected by a GPS satellite navigation system. Due to combination of dynamic determination of intermediate nodes and a store-carry-forward method, higher transmission ratio and shorter end-to-end transmission delay are achieved even with high mobility and sparse distribution of nodes.